Anti-dumping and countervailing procedures - use or abuse? : implications for developing countries. - Neufeld, Inge Nora (UN New YorkUS, 2001)
Analyses distribution, duration and final outcomes of antidumping (AD) and countervailing (CV) measures investigations. Concludes that anti-dumping and countervailing actions have resulted in significant reductions in trade volumes and market shares. Analyses the WTO Agreements themselves and finds that many of the negative effects of AD and CV measures are not adequately addressed.